Huo yuan jia Fearless - Kong, Bill; Yu, Ronny; Focus Features; Hero China International ([Universal City, CA] : Buena Vista Home Entertainment (distributor), 2006)
Huo Yuan Jia agrees to represent China in an international competition against a British boxer, a Spanish swordsman, a Belgian soldier, and a Japanese martial artist
Title from title screen
Director of photography, Poon Hang Sang ; editors, Virginia Katz, Richard Learoyd ; music, Shigeru Umebayashi ; costume designer, Thomas Chong ; visual effects supervisor, Victor Wong ; screenplay by Chris Chow, Christine To
Cast: Jet Li, Shido Nakamura, Betty Sun, Yong Dong, Hee Ching Paw, Yun Qu, Collin Chou, Nathan Jones, Brandon Rhea
DVD Format
Optional subtitles in Chinese, Indonesian or Malay
Keywords: Martial artists -- China -- Drama; Hand-to-hand fighting, Oriental -- China -- Drama; Revenge -- Drama; Feature films -- China; Martial arts films